Language and identity: Hong Kong students' language attitudes since the Umbrella Movement - Wong, King Yuen (2015)
Abstract Previous empirical studies conducted on Hong Kong’s linguistic situations suggest that the roles and statuses of Cantonese and English continue to be stable in Hong Kong. Putonghua (also known as Mandarin) starts to have an ever-increasing influence in the city and has begun to take root since the political handover in 1997. Lai (2011) expects that Hong Kong people will develop their identities at local, national and international levels and Hong Kong will see a more balanced equilibrium between Cantonese, Putonghua and English. Despite the integration of Hong Kong into China spanning social, economic and political spheres in recent years, the continuing convergence of Hong Kong and Chinese identities may not materialise among Hong Kong people as predicted. Rather intensified cross-border conflicts may breed deepening alienation towards China and growing localism in Hong Kong. Such anti-China sentiments and localist ideologies manifested themselves in the months-long Umbrella Movement in 2014 where student protesters called for democracy and political reforms. Given the inextricable link between language and identity, this paper hopes to take into account all these current socio-political developments in Hong Kong and bring in new dimensions to the discussion about language attitudes and cultural identity. The current research partially replicated Lai’s (2011) similar study with the aim of reporting any differences in the findings. Unlike the respondents in Lai’s study, those in the current study were secondary school students born after Hong Kong became a Chinese special administrative region in 1997 and had no experience of Hong Kong under colonial rule. The post-colonial generation’s cultural identifications and their attitudes towards Cantonese, Putonghua and English may provide insight into how policies can be formulated for Hong Kong’s gradual political and linguistic unifications with China. Seventy-five questionnaires were analysed and six individual interviews were conducted. The results reveal that the respondents of the current study had greater identification with Hong Kong but less with Mainland China, compared to their counterparts in Lai’s (2011) study. They also showed significantly more positive attitudes towards Cantonese but less towards Putonghua than their predecessors. With respondents of the current study who were born in the post-colonial era identifying themselves more as Hong Kongers than Chinese and inclining more towards the local vernacular than the national language, the socio-political and pedagogical impacts should not be neglected.